Quality of Service and Control Governor’s Recommendation Utilization of Northern Bandung Area in the Office of Capital Invesment and One Stop Integrated Service the Province of West Java - Irvan Niko Firmansyah; Soleh Suryadi; Edy Jusuf Sp (International Journal of Science and Society, 2020)
Government is an organization that has full responsibility on the improvement of public service quality. Consequently service becomes the prior task of organization’s officials as civil and public servants. There are 197 licenses and non-licenses public services. Therefore, it is important to maintain and improve service quality continuously. Meanwhile, the existing service quality hasn’t shown significant result. It can be viewed from public complaints on the publication process of governor’s recommendation of land use in North Bandung Region, yet there were a lot of field control that its implementation irrelevant with the recommendation. Complaints, indictments and inappropriateness recommendation in the field need to be minimized in order to optimize service quality and control conducted by West Java Provincial Government on the publication process of governor’s recommendation of land use in North Bandung Region. Accordingly, researcher would like to conduct further study on how Service Quality and Control of Governor’s Recommendation of Land Use in North Bandung Region performed by West Java Provincial Government, as well as to study strategies that can be applied in order to improve service quality. This research applied qualitative study using snow ball technique to objects of study, i.e. public service administrator; public service customer; public service observer, primarily those who are involved in the legalization of governor’s recommendation of land use in North Bandung Region. The data were obtained through interview and deep analysis using triangulation observers. The research of the study reveals that the inconsistency of service quality is influenced by 10 dimensions, i.e. tangibles, reliability, responsiveness, courtesy, credibility, security, access, communication and understanding consumer. On the other hand, environment control, risk assessment, control activities, information and communication, yet monitoring control are determinant factors in controlling governor’s recommendation of land use in North Bandung Region. It is done by applying strategy that implement technology, innovation and operation approach. From the research, it is found new dimensions, they are: institutional coordination, supervision, collaboration, prosecution and policy diversification through GSMALL Collaboration Model (Government, Society, Media, Academic, and Law Enforcement).